Penentuan Model Kecepatan Seismik 1-D di Pulau Lombok - I Gusti Ketut Satria Bunaga; Mohammad Syamsu Rosid; Titi Anggono; Ardhianto Septiadhi (Jurnal Penelitian Pendidikan IPA, 2023)
The interpretation of local geology structure can be done effectively by using an appropriate local seismic velocity model. It is suitable to implement in Lombok Island that the local fault activity near Mount Rinjani caused the 2019 East Lombok Earthquake. This study determines and updates the 1-D seismic velocity model using the VELEST by applying the Coupled Hypocenter-Velocity method. The 2010-2022 earthquake data from the catalog of BMKG is used for this study. A total of about 166 events (M â‰¥ 4) and 20 seismic stations in Lombok and surrounding areas are utilized in this study. The local model (Koulakov) and global (AK-135) are selected as the initial model. The double-difference method is also used to test both velocity models refining the hypocenter location. The results show that the updated Koulakov model has a high relevance in representing the crustal structure of Lombok Island according to the parameters of RMS value, uncertainties hypocenter, and seismic interpretation. It demonstrates not only the local geology condition but also a more reliable seismic velocity model in the region of Lombok Island. This model can be used as a reference for interpreting the better geological structure.